Psychometric deficits in autoimmune encephalitis: A retrospective study from the Australian Autoimmune Encephalitis Consortium. (20th May 2022) - Griffith, Sarah; Wesselingh, Robb; Broadley, James; O'Shea, Marie; Kyndt, Chris; Meade, Catherine; Long, Brian; Seneviratne, Udaya; Reidy, Natalie; Bourke, Robert; Buzzard, Katherine; D'Souza, Wendyl; et al.
Abstract: Background and purpose: Despite the rapid increase in research examining outcomes in autoimmune encephalitis (AE) patients, there are few cohort studies examining cognitive outcomes in this population. The current study aimed to characterise psychometric outcomes in this population, and explore variables that may predict psychometric outcomes. Methods: This retrospective observational study collected psychometric data from 59 patients across six secondary and tertiary referral centres in metropolitan hospitals in Victoria, Australia between January 2008 and July 2019. Frequency and pattern analysis were employed to define and characterize psychometric outcomes. Univariable logistic regression was performed to examine predictors of intact and pathological psychometric outcomes. Results: Deficits in psychometric markers of executive dysfunction were the most common finding in this cohort, followed by deficits on tasks sensitive to memory. A total of 54.2% of patients were classified as having psychometric impairments across at least two cognitive domains. Twenty‐nine patterns were observed, suggesting outcomes in AE are complex. None of the demographic data, clinical features or auxiliary examination variables were predictors of psychometric outcome. Conclusions: Cognitive outcomes in AE are complex. Further detailed and standardized cognitive testing, in combination with magnetic resonance imaging volumetrics and serum/cerebrospinal fluid biomarkers, is required to provide rigorous assessments of disease outcomes.